2010
DOI: 10.1111/j.1365-2915.2010.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structuring of the tsetse Glossina tachinoides resulting from landscape fragmentation in the Mouhoun River basin, Burkina Faso

Abstract: Abstract. The impact of landscape fragmentation resulting from human-and climatemediated factors on the structure of a population of Glossina tachinoides Westwood (Diptera: Glossinidae) in the Mouhoun River basin, Burkina Faso, was investigated. Allele frequencies at five microsatellite loci were compared in four populations. The average distance between samples was 72 km. The sampling points traversed an ecological cline in terms of rainfall and riverine forest ecotype, along a river loop that enlarged from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…At the most disturbed site, the few tsetse captured during the rainy season may have been flies dispersing from more conserved areas, as suggested by the absence of genetic structure between populations at Douroula and Boromo (Koné et al, 2010).…”
Section: Influence Of Site On Species Diversity and Abundancementioning
confidence: 95%
See 2 more Smart Citations
“…At the most disturbed site, the few tsetse captured during the rainy season may have been flies dispersing from more conserved areas, as suggested by the absence of genetic structure between populations at Douroula and Boromo (Koné et al, 2010).…”
Section: Influence Of Site On Species Diversity and Abundancementioning
confidence: 95%
“…agrestis. Immigration of G. tachinoides, as demonstrated using genetic analyses (Koné et al, 2010), may have introduced the parasite. Atylotus agrestis, which was unequivocally shown to transmit T. vivax at a high rate in experimental conditions in the same geographic area (63% in 13-20 days) (Desquesnes & Dia, 2004), may then have amplified transmission of the parasite.…”
Section: Seasonal Dynamics Of Trypanosomoses Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In population genetics studies of tsetse flies using microsatellite markers, heterozygote deficits have frequently been reported Kone et al, 2010Kone et al, , 2011Mélachio et al, 2011;Ravel et al, 2007;Solano et al, 2000Solano et al, , 2009. In these studies, the use of several methods of analysis have shown that the Wahlund effect, the presence of null alleles and of short alleles dominance were probable sources of the artificial heterozygote deficits.…”
Section: Discussionmentioning
confidence: 98%
“…G. tachinoides population sizes seem to be relatively large with important migration rates and effective population sizes, probably due to their greater ecologic tolerance, i.e. xerophily (Kone et al, 2010(Kone et al, , 2011. On the contrary, reproductive units seem smaller in Glossina palpalis sub-species, to the extent that samples from nearby traps belong to several different populations Kone et al, 2011;Ravel et al, 2007;Solano et al, 2000Solano et al, , 2009.…”
Section: Introductionmentioning
confidence: 91%